From Blofeld to Moneypenny : gender in James Bond - Gerrard, Steven (Bingley, U.K. : Emerald Publishing Limited, 2020)
The world of James Bond is complex and ever growing. The British secret agent started off life as a semi-fictional, part-biographical character in Ian Fleming's 1953 novel, Casino Royale. Since then, 007 has captured the minds and hearts of a worldwide audience, and the franchise is now available over multiple media platforms, including movie, comic strips, games, graphic novels and fashion statements. This edited collection examines the role that gender has played across the platforms that the James Bond franchise now occupies. Each chapter investigates gender-approaches through a variety of case studies, including Bond, his boss M, and Miss Moneypenny, the songs and title sequences, the villains, computer games, 'Lad's Mags', and the fashions of the era. Looking beyond the Bond Girl, expert editor Steven Gerrard brings together a cast of contributors that investigate not only femininity, but also masculinity when it comes to the world's best-known agent - a man with a license to kill. In a rapidly changing world where gender boundaries are being eroded, this edited collection investigates the changing and challenging roles that gender has undergone in the franchise. By using a series of case studies, and employing theoretical modes linked to close analysis, each chapter clearly demonstrates how and why the world of James Bond is important in reflecting the changing gender roles within modern society.
Introduction Steven Gerrard Part One: Mr Kiss Kiss Bang Bang -- Chapter 1: Keeping the British end up: James Bond and the varieties of Britishness / James Chapman -- Chapter 2: The Patriotic Spy: For Queen, Empire and Dry Martinis / Jennie Lewis-Vidler -- Chapter 3: Adapting the male hero: the comic strip adventures of James Bond / Robert Shail -- Chapter 4: Seven James Bonds at Casino Royale /Wickham & Clayton -- Chapter 5: Fitting Fleming's hero like a Savile Row suit: The tailoring of James Bond / Llewella Chapman Part Two Bond Girls, Bond Women -- Chapter 6: The Soviet Woman in Bond Films / Helena Bassil-Morozow -- Chapter 7: Babes and Bullets: The representation of gender in Bond themes and title sequences / Shelley O'Brien -- Chapter 8: Her Word Was Her Bond: Johanna Harwood, Bond's First Woman Screenwriter / Melanie Williams -- Chapter 9: Her Majesty's Secret Service: Judi Dench's M and her monarchial tenure / Charlotte Allan -- Chapter 10: Moneypenny: Jane or Eve? Ethos, pathos and the woman behind all Bonds /Octavio Aragão Part Three: Nobody Does It Better -- Chapter 11: Loaded Magazines: James Bond and British men's mags in the Brosnan era / Claire Hines and Stephanie Jones -- Chapter 12: Blofeld Steven Gerrard -- Chapter 13: Standard Operating Procedure. Boys with Toys: Hackers, Gamers and the Hegemony of Play in GoldenEye / Dean Bowman -- Chapter 14: Miss Moneypenny and the Friend-Zone: The Indispensable and Sexually Unavailable 'Bond Girl' / Janelle Vermaak and Natalie Le Clue -- Chapter 15: Celebrating 10 years of Idris Elba becoming James Bond any second now: fandom, ownership, and the alt-right / Renee Middlemost.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Bond, James -- (Fictitious character) -- In literature; James Bond films; Characters and characteristics; Performing arts, Film, Genres, Action & Adventure; Film: styles & genres